Health‐related experiences of adults with chronic cough: Empirical research mixed methods - Michael Weiner; Jessica Weaver; Tayler Gowan; Sean A. Baird; Monica Huffman; Paul Dexter; Vishal Bali; Jonathan Schelfhout; Ashley Griffith; Jacob Pell; Ishita Doshi; Tasneem Talib (Nursing Open, 2023)
Abstract Aim To describe adults' health‐related experiences with chronic cough. Design Survey and interviews. Methods Participants completed questionnaires and interviews, to explore chronic cough's impact and management. Data Sources Patients aged 18–85 years with at least three cough‐related encounters within 56–120 days. Results Forty‐one patients were surveyed. Mean cough severity was 4.5 (scale 0–9). Chronic cough‐related problems included embarrassment (66%), fatigue (56%), and anxiety or depression (49%). Testing was judged insufficient by 44%. Only 28% were satisfied with treatment; 20% reported abandoning treatment due to ineffectiveness. Interview themes (N = 30) included frustration with diagnostic uncertainty, and feelings of therapeutic futility. Some reported psychological distress. Work and socializing were commonly disrupted. Conclusion Diagnostic uncertainty, perceived limitations of testing, and treatment failures suggest needs for better approaches to evaluating and treating chronic cough. Special attention to identifying and addressing mental health issues appears warranted.